ظاهرة الإيقاع الخارجي في قصائد شوقي الوطنية : (The Phenomenon of External Rhythm in Shawqi's Patriotic Poems) - (Nasreldin Ibrahim Ahmed Hussien), نصر الدين إبراهيم أحمد حسين; (Mohammed Shareef Mohammed Hafees), محمد حفيز بن محمد شريف (At-Tajdid - Intellectual Refereed Journal, 2021)
Abstract Critics normally investigate the rhythm, as one of the most important criteria in analyzing the Arabic poems in general. Hence, this study aims to explore the external musical rhythm in Ahmed Shawqi's patriotic poems that focuses on the nation's concerns, aspirations and pains. The researcher made use of the descriptive analytical approach to uncover the artistic characteristics and the aesthetic features related to poetic meters and rhymes as well. The study found that Shawqi, as a poet who preserved the approach of 'School of revival' employed the poetic meters attributed to Khālīl, with greater reliance on Baḥr al-kāmil in his patriotic poem. In addition to that, Shawqi often chose selected consonants to be the ending of every lines of his poem. He took advantage from art of Tawshīh in the poems to diversify the ending of the lines, relying on the medium density of the rhythm in the end of his lines which often came in certain stipulated forms; as we only found some minor flaws. The poet also showed his ingenuity through his commitment to some unnecessary rhyme in the ending of his poetic lines, and he had shown his excellence in using some leonine rhymes as the ending of his poetic lines in most of his nationalistic poetry. Keywords: Ahmed Shawqi, patriotic poems, External rhythm, Khalilian poetic meters, ending of lines, Rawiy, Tawshih, Leonine rhyme.